ATTITUDES OF FOOTBALL PLAYERS OF DIFFERENT SPORTS EXPERIENCE ON THE ALLOWED MEANS OF STIMULATING RECOVERY - Miroslav Smajić; Dejan Madić; Borislav Obradović; Zoran Milošević; Slavko Molnar; Bogdan Tomić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
Allowed stimulating means of recovery are considered substances and physiological processes that act through the increase in performance athletes and to more efficient recovery and improvement of sports results, which are very difficult to achieve the usual training methods of training, and it can be considered useful until used as a supplement to training. If the rational use, it significantly increases the resistance of the organism in Training athletes and competition loads and favorably affect the elimination of general and local fatigue. The aim of the research consists of testing and analyzing the attitudes of different sports experience on the allowed means of stimulating recovery. The sample of examinees consists of 120 footballers of different sports experience (I group (62) - 4-8 years of sports experience, II group (58) - 9-14 years of sports experience). The sample of variables consists of the system of 10 attitudes (claims), and each attitude (claim) consists of 5 verbal categories (marked from -2 to +2). To determine multivariate and univariate significance of differences between footballers of different competition ranks multivariate analysis of variance (MANOVA) and univariate analysis of variance (ANOVA) have been applied. Generally it can be concluded that players with less experience attach less importance to some of the allowed recovery stimulus, and that the level of information increases with sports experience.